2008
DOI: 10.1242/jcs.035626
|View full text |Cite
|
Sign up to set email alerts
|

Flagellum elongation is required for correct structure, orientation and function of the flagellar pocket in Trypanosoma brucei

Abstract: In trypanosomes, the flagellum is rooted in the flagellar pocket, a surface micro-domain that is the sole site for endocytosis and exocytosis. By analysis of anterograde or retrograde intraflagellar transport in IFT88RNAi or IFT140RNAi mutant cells, we show that elongation of the new flagellum is not required for flagellar pocket formation but is essential for its organisation, orientation and function. Transmission electron microscopy revealed that the flagellar pocket exhibited a modified shape (smaller, dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 42 publications
(77 reference statements)
4
63
0
Order By: Relevance
“…The flagellar pocket region also appeared normal in CC2D RNAi cells. Previous reports suggested that a new flagellum and a new FAZ play important roles in flagellar pocket organization, basal body positioning and segregation (Absalon et al, 2008;Kohl et al, 2003;Lacomble et al, 2010). Whereas elongation of the new flagellum, with its distal end anchored to the old flagellum, pushes the new basal body away to the posterior end of the cell, the new FAZ might restrain the segregation and hold the new basal body in place.…”
Section: Discussionmentioning
confidence: 99%
“…The flagellar pocket region also appeared normal in CC2D RNAi cells. Previous reports suggested that a new flagellum and a new FAZ play important roles in flagellar pocket organization, basal body positioning and segregation (Absalon et al, 2008;Kohl et al, 2003;Lacomble et al, 2010). Whereas elongation of the new flagellum, with its distal end anchored to the old flagellum, pushes the new basal body away to the posterior end of the cell, the new FAZ might restrain the segregation and hold the new basal body in place.…”
Section: Discussionmentioning
confidence: 99%
“…The first stage of this process is maturation of the probasal body, which gains the capacity to nucleate a new flagellum (Lacomble et al, 2010). This maturation can be tracked with antibodies against trypanosome basal body component (TBBC) protein, a coiled coil protein shown to associate selectively with mature basal bodies (Dilbeck et al, 1999;Absalon et al, 2008). After maturation, the two basal bodies assemble new probasal bodies, completing the duplication cycle (Sherwin and Gull, 1989).…”
Section: Tbplk Depletion Does Not Affect Basal Body Duplication or Mamentioning
confidence: 99%
“…In intraflagellar transport mutants, where the growth of a new axoneme is prevented, basal body segregation still occurs to some extent (Absalon et al, 2008;Davidge et al, 2006). Indeed, after segregation, a flagellar sleeve representing an 'empty' new flagellum lies on the correct posterior side of the old flagellum (Davidge et al, 2006).…”
Section: Basal Body Migration and Cell Morphogenesismentioning
confidence: 99%